Investigating the relationship between sleep and emotion amongst club rugby players - Rawoot, Sameenah (Department of Psychology, 2024)
In rugby players, both sleep and the ability to regulate emotion are essential to performance and well-being. For example, poor sleep quality is associated with competition losses, and the inability to regulate emotions such as impulsivity and aggression is detrimental during play and could lead to injury. Critically, successful emotion regulation is fostered by healthy sleep and evidence shows that poor sleep quality is associated with poor emotion regulation. Therefore, poor sleep quality in this group of individuals may contribute to emotion dysregulation. Other factors that complicate the relationship between sleep and emotion regulation among rugby players include concussion experience, depression, alcohol use, and drug use, because of their independent influence on both sleep and emotion regulation. The purpose of the current study was therefore to investigate the relationship between sleep quality and emotion regulation ability in rugby players who may or may not have a history of concussion, depression, alcohol use, and/or drug use. The current study included a group of participants who played club rugby (Rugby group; n = 21), and a group of sportsmen who did not play any contact sport (Non-Contact Sport group; n = 21). This online study utilized a survey, which included questions regarding demographics, alcohol and drug use, presence and severity of depressive symptoms, history of concussion, sleep quality, and emotion regulation ability. I used one-tailed t-tests, non-parametric measures, and multiple regression analyses to assess the relationship between sleep quality and emotion regulation ability, while controlling for history of concussion, depressive symptoms, alcohol use, and drug use. Results indicated that the Rugby group displayed significantly poorer sleep quality, specifically with respect to sleep disturbance, than the Non-Contact Sport group, p = .05, d = .516. The Rugby group also reported significantly higher emotion regulation difficulties than the Non-Contact Sport group, p = .006, d = 14.36. The analyses also showed that a history of concussion, group, depressive symptoms, alcohol use, and drug use, did not have a significant effect on emotion regulation, whereas sleep disturbance did. The results indicate that there is a strong negative correlation between sleep quality and emotion regulation in club rugby players. The implications of these results indicate that regardless of group allocation (i.e., participating in contact sport vs non-contact sport), sleep disturbance, is the primary factor in determining emotion regulation ability. The results suggest that whether one participates in contact-sport, or non-contact sport, good sleep quality should be a priority, and interventions should be in place for those who struggle with sleep disturbance in particular. However, the generalizability of these results are limited by the small sample size. Key words: concussion, rugby, sleep quality, emotion regulation